INCOME AND ECONOMIC GROWTH FROM LEGAL ENVIRONMENT: EMPIRIC ANALYSIS - Nargiza Rabimovna, Fayzieva (International Journal of Business, Law, and Education, 2020)
The following is an econometric analysis of corporation income tax and its impact on the country’s GDP. An analysis of the literature on the topic is first followed by the results of an empirical analysis. According to the results of the study, the short-term impact of corporation income tax on economic growth is high. All the results are obtained at the end of the work.